New insights related to the flotation of covellite in porphyry ores. (1st December 2021) - Botero, Yesica L.; Serna-Guerrero, Rodrigo; López-Valdivieso, Alejandro; Benzaazoua, Mostafa; Cisternas, Luis A.
Highlights: Covellite flotation was studied using pure natural covellite and porphyry ores. Covellite has a natural flotation yield with recovery around 55% and is not pH-dependent. Collector type, collector concentration, and pH are key factors for covellite-pyrite separation. IPETC can be used as a selective and bulk collector for covellite-pyrite separation. PAX can be used as a bulk collector for covellite-pyrite flotation. Abstract: Covellite usually occurs accompanying other copper minerals, like chalcopyrite and chalcocite, but there are few studies on covellite flotation. The effect of collectors O-isopropyl-N-ethyl thionocarbamate (IPETC) and potassium amyl xanthate (PAX) and pH on covellite and pyrite flotation was investigated through a Hallimond tube test using pure covellite and pyrite and a Denver cell test using porphyry ore. Pure covellite and pyrite were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR). Moreover, the covellite was characterized using scanning electron microscopy coupled to energy dispersive spectroscopy (SEM-EDS). Porphyry ore was characterized by automated mineralogy using scanning electron microscopy (QEMSCAN®). Design of experiments was utilized to identify the factors with a statistical influence (ANOVA) and obtain the optimal flotation conditions using response surface methodology (RSM) and desirability function. ANOVA test demonstrated that the factors that influence covellite behavior are the collector type and dosage. The results obtained on pure minerals shows that with a high PAX concentration and low pH, it is possible to carry out bulk flotation with recoveries of 93% covellite and 90 % pyrite, and with a low IPETC dosage and high pH, it is possible to get a selective flotation with around 81% covellite and 20% pyrite recoveries. These results were determined using RSM and desirability function, and corroborated with the Hallimond tube test. Then, the flotation results of mixture covellite-pyrite show that selective flotation is feasible with IPETC at alkaline pH with a low dosage displaying recoveries of 97 % covellite and 53 % pyrite. Also, bulk flotation is feasible with PAX at a pH of 8 and a high collector concentration with recoveries of 96% covellite and 88% pyrite. The results show that covellite recovery is not pH-dependent. The Denver cell test with a porphyry ore shows a selective flotation with IPETC at a pH of 11 with a low collector dosage (5 g/ton), achieving recoveries of 92% covellite and 39% pyrite. Also, recoveries of 85% covellite and 75% pyrite were observed for a bulk flotation with IPETC at pH = 8 at the same collector dosage. Therefore, the IPETC can be used as a selective or bulk collector when varying the pH and collector concentration. These results demonstrate that covellite flotation performances remain constant over a wide range of pH values, which allows a selective separation from other sulfides such as pyrite.